A Neoteric Fractional Image Encryption Methods Based On Logistic Mapping - Chauhan, Shweta; Kumar Mishra, Pawan (International Journal of Computer Sciences and Engineering, 2025)
Cryptography is a intelligence to absorb the ambush of the accession by barter abstracts or admonition into advisement form, so the bulletin cannot be recognized. Today, there are abounding algorithms acclimated for the for Image encryption, but the chaotic encryption methods accept a acceptable aggregate of speed and high security. In abounding years, the chaotic based cryptographic apportioned accept been acceptable some new and abstruse means to advance defended Image encryption techniques. The chaos-based encryption schemes are composed of two steps: chaotic confusion and pixel diffusion. We aboriginal accord a explain addition into chaotic Image encryption and again we investigate some important backdrop and behavior of the logistic map. The logistic map, alternate trajectory, or random-like fluctuation, could not be acquired with some best of antecedent condition. Therefore, a blatant logistic map with accretion arrangement babble is introduced.